Thymol Improves Brain Functional Outcomes after Cerebral Ischemia-Reperfusion Injury by Regulating p38 MAPK Associated Apoptosis Signalling Pathway - Mukkudiahgari, Hima Saila; Kudamala, Ramesh Reddy; Thakur, Santhrani (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Thymol, a monoterpene phenolic compound and an essential oil extracted from Tachyspermum ammi (ajwain) has been shown to possess multiple therapeutic potentials as anti-inflammatory, antioxidant, antihyperlipidemic, antiapoptotic, antitumor agent against neurological, cardiovascular, gastrointestinal and malignant diseases. Objectives The current investigation aimed to determine whether thymol could protect rats from cerebral ischemia reperfusion injury by preventing Bilateral Common Carotid Artery Occlusion (BCCAO). Materials and Methods: After 14 days of pretreatment with thymol at the doses of 50 mg/kg, p.o and 100 mg/kg, p.o. respectively, Albino Wistar rats (200-250 g) were subjected to BCCAO for 1 hr followed by 22 hr reperfusion (I/R). The levels of protein carbonyl content, Myeloperoxidase (MPO) were measured in brain tissue homogenate. Utilising western blotting, the expression levels of TNF-α, Interleukin 10 (IL-10) anti-inflammatory cytokines, pro-apoptotic mediators Bax and Caspase 3 and anti-apoptotic mediator Bcl-2 were assessed. Results and Discussion Reduction in levels of protein carbonyl content and Myeloperoxidase (MPO) was observed in thymol groups. Thymol pretreated rats showed significant (p<0.01) downregulation in the expressions of TNF-α and inhibited phosphorylation of p38 MAPK. In parallel, the expressions of IL-10 were upregulated significantly (p<0.01). Thymol exerted anti-apoptotic effect as reflected by decreased expression of the key downstream executioner caspase-3 and Bax, which is probably mediated by significant upregulation of expression of Bcl-2. Conclusion Thymol is endowed with neuroprotection against global cerebral ischemia reperfusion injury which may be probably mediated by attenuation of inflammatory and apoptotic mechanism via p38 MAPK signaling pathway.
Keywords: Anti-inflammatory activity; p38 MAPK; Anti-apoptotic activity; Ischemic reperfusion injury; Thymol.